Understanding the thermal, mechanical and electrical properties of epoxy nanocomposites - Sarathi, R.; Sahu, R.K.; Rajeshkumar, P.
In the present work, the electrical, mechanical and thermal properties of epoxy nanocomposite materials were studied. The electrical insulation characteristics were analyzed through short time breakdown voltage test, accelerated electrical ageing test, and by tracking test. The breakdown voltage increases with increase in nano-clay content up to 5 wt
Keywords: EPOXY RESIN; NANOCOMPOSITES; NANOCLAY; INSULATION; BREAKDOWN; CONTACT ANGLE; WEIBULL DISTRIBUTION